OC-027 IS THERE A CORRELATION BETWEEN TYPE OF PROSTHESIS FIXATION IN T.A.P.P. AND AFTER SURGERY RECOVERY? OUR CENTER EXPERIENCE. (13th October 2022) - Gianazza, S; Guzzetti, L; Grappolini, N; Odeh, M; Scorza, A; Palillo, A; Gerosa, S; Morabito, M; Inversini, D; Ietto, G; Carcano, G
Abstract: Aim: A retrospective study was carried out on patients treated for bilateral inguinal hernia with TAPP technique by the department of Urgency Surgery and Transplantation of Varese's hospital in order to investigate the VAS one month after surgery and functional recovery in two groups of patients. Material and Methods: 38 patients treated in the last year were enrolled, dividing them in two groups: those who received a single fixing material (reabsorbable clips) and those with a double fixing material (reabsorbable clips and glue). Primary end point was the post-operative pain using the VAS scale at one month. Secondary end-point was the return to daily activities and work in days. The Mann-Whitney test with p-value set< 0.05 was used. Results: The single fixing material group shown a 1-month VAS of 0.57 ±1, versus 1.43±4 of the second group (p-value<0.05); with a return of daily activities in 4.92± 8 days, versus 8.06 ± 11 days (p-value<0.05). In addition, analyzing the subpopulation of still active workers (28 of the 38 patient), it was assessed the working back timing. The positioning of only reabsorbable clips, compared with a double fixing material, ensured a faster return to work in 8.2 ±10 days versus 20 ± 30 days (p-value<0.05). Conclusions: Fixing the prosthetic mesh with resorbable clips alone, could lead to a more rapid resumption of daily and work activities, with less pain one month after surgery.